Fungsi Gerak Lansia dengan Tingkat Kemandirian Lansia - Badaruddin Badaruddin; Abubakar Betan (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction: the function of joint motion connects one bone to another. Independence, the ability to carry out daily activities or tasks alone or with the stages of development and capacity. Aim; determine the relationship between joint function and the level of independence of the elderly. Method: used correlation analysis with a cross-sectional approach. For the population of all elderly people aged > 60 years, sampling by purposive sampling technique met the inclusion criteria. Data collection with goniometer measuring scale questionnaire instruments and observation sheets. Results: showed that the value of p = 0.339 <0.05. Conclusion; that there is no relationship between the movement function of the elderly and the level of independence of the elderly